urbanship - Grigoryeva, Elena (project baikal, 2015)
A native Polynesian can identify this or that place of the archipelago by tasting the Ocean water. In the fog of the night, with his eyes closed, he is engaged in a dialogue with his environment; he comprehends it and trusts in it.Since the time when Project Baikal devoted the main topic of the issue to environment and advertising, a lot of things concerning our cities have changed, some of them for the better. It is increasingly recognized that the condition of urban environment is of the essence, that it can make the city attractive and competitive, and that it has an effect on the quality of life. The capital city sets an example: bright designs of embankments, boulevards and squares are realized quickly and to the highest standard. Improvements in Moscow are obvious.And what about Irkutsk?The awareness has increased. Now not only the creative class, but also the city administration calls for renovation of green parks, improvements and planting. Not only in word, but in deed. New miniparks are appearing. Sometimes they are more or less cozy, sometimes they are cold and senseless. Almost in each case they are not integrated into a system. Design codes are being worked out for the main street.Is this enough? Is the urban environment on the way to recovery? Are we, the urban dwellers, going to find a common language with Genius Loci of the place we inhabit? How soon will we manage to harness the wild advertising, to give priority to pedestrians, and to reanimate the sixtiers’ brilliant ideas about the balance between the linear and the centric urban planning principles?Our understanding of the sense and the essence of urban environment is still insufficient. This term is too indistinct and multivalent to build up theory and practice of urban life management on its basis.We introduce a new term – URBANSHIP – and make it the title of the issue. Urbanship is a way to see the city, its problems and processes in the light of relationship between a human being and Genius Loci. We raise a question of how to work out a method, but not a collection of guidelines on improvements of urban environment. Each place of the city has its own Genius Loci, like each island of the archipelago has its own taste of water. Even the most efficient decisions are inimitable; we can replicate only a method (yet to be comprehended and formulated)…